Manufacturing method of abrasives
The method of manufacturing grinding materials by preparing coal ash, adding water, classifying, and bagging in a wet state addresses the inefficiencies of conventional drying methods, reducing dust generation and improving moisture retention for enhanced wet blasting performance.
Patent Information
- Application Number
- JP2023215031
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-12-20
AI Technical Summary
Conventional grinding materials are dried during manufacturing, leading to dust generation and inefficiencies, as they are not produced in a wet state.
A method for manufacturing grinding materials by preparing coal ash, adding water to stir it, classifying the coal ash, and bagging it in a wet state, eliminating the need for drying.
This method allows for the production of grinding materials in a wet state, reducing dust generation during manufacturing and improving moisture retention during use, enhancing the efficiency of wet blasting processes.
Smart Images

Figure 0007650578000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an abrasive used in wet slurry blasting. [Background technology]
[0002] A blasting method has been known in which an abrasive material containing sand is sprayed with compressed air onto the painted surfaces of steel structures such as bridges to remove rust and old paint and clean the surface of the steel.
[0003] Blasting methods are generally classified into air blasting, vacuum blasting, and wet blasting. Of these, wet blasting is a method in which water and an abrasive are mixed and then blasted, and has become more widely used in recent years due to its advantage of generating less dust.
[0004] For example, Patent Document 1 discloses a blasting material for wet blasting, which contains 5 to 30 mass % moisture relative to alumina, garnet, silica sand, glass beads, silicon carbide or slag as an abrasive and is pre-adjusted so that all abrasive particles are wet. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2012-121121 A Summary of the Invention [Problem to be solved by the invention]
[0006] Known abrasives include ferronickel slag, fused alumina, almandite garnet, copper slag, and steel grit. However, these conventional blasting materials are mixed with water just before blasting, and the abrasives themselves are not manufactured in a wet state. In other words, conventional abrasives are dried in a dryer during the manufacturing process, which requires a lot of time for drying and generates dust.
[0007] Therefore, an object of the present invention is to provide a method for producing an abrasive which is produced in a wet state without drying. [Means for solving the problem]
[0008] In order to achieve the above-mentioned object, the manufacturing method of an abrasive material of the present invention includes a step of preparing coal ash, a step of adding water to the coal ash and stirring the coal ash, a step of classifying the coal ash that has been added with water and stirred, and a step of bagging the classified coal ash. Effect of the Invention
[0009] In this way, the manufacturing method of the abrasive of the present invention includes a step of preparing coal ash, a step of adding water to the coal ash and stirring the coal ash, a step of classifying the coal ash that has been added with water and stirred, and a step of bagging the classified coal ash. With such a process, the abrasive can be manufactured while keeping the coal ash, which is the raw material, in a wet state without drying it. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is an overall view of an abrasive manufacturing system. [Diagram 2] FIG. 2 is a flow diagram of a method for manufacturing an abrasive. [Diagram 3] FIG. 1 is an explanatory diagram of a wet slurry blasting method. [Figure 4] 1 is a table showing test results, where (a) is a table showing the particle size test results after the first classification process, (b) is a table showing the unit volume weight results, and (c) is a table showing the moisture content test results. [Diagram 5] 1 is a table showing particle size test results of clinker ash before and after second process classification. [Figure 6] 1 is a table showing the results of a blast test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present invention will be described with reference to the drawings. However, the components described in the following embodiments are merely examples, and are not intended to limit the technical scope of the present invention.
[0012] (Abrasives manufacturing system) First, the overall configuration of the abrasive manufacturing system S will be described with reference to Figures 1 and 2. As shown in Figure 1, the abrasive manufacturing system S is mainly composed of a dissolution tank 10 that receives coal ash as a raw material and is supplied with water and stirred, a wet two-stage vibration sieve 11 for classifying the pressure-fed coal ash, a lower water tank 12 that receives the fine particles and water that have passed through the vibration sieve 11, and a dehydration tank 13 that contains a dehydration bag 13a that receives the fine particles and water pressure-fed from the lower water tank 12.
[0013] The dissolution tank 10 is, for example, a cylindrical container, into which coal ash (clinker ash or IGCC slag) as pre-classified material and water are charged and stored (steps S1 and S2). Furthermore, the coal ash and water are mixed by rotating the stirring blades 10a using a motor 21 installed on the dissolution tank 10 (step S3). Here, the ratio of the pre-classified material to water in the dissolution tank 10 can be, for example, about 1:3.
[0014] A constant amount of water is maintained in the dissolution tank 10 by circulating overwater from the dewatering tank 13 described below. The size (diameter and height) of the dissolution tank 10 is preferably determined according to the amount of processing. Specifically, the water level needs to be kept above the agitator blades 10a so that the pre-classification material and water can be easily mixed.
[0015] Here, it is preferable to use clinker ash (CA) or IGCC slag as the coal ash prepared in this embodiment. Clinker ash (CA) is ash that is obtained by recovering, dehydrating, and pulverizing lumps of coal ash that fall to the bottom of a boiler, among the coal ash generated when coal is burned. IGCC slag (coal gasification slag) is glassy slag that is generated as a by-product in integrated coal gasification combined cycle (IGCC).
[0016] The dissolution tank 10 and the wet-type vibrating sieve 11 are connected by piping, and a slurry-like mixture of the pre-classified material and water is pumped from the dissolution tank 10 to the vibrating sieve 11 by the pump 22 (step S4).
[0017] The vibrating sieve 11 as a wet classifier is a two-stage type consisting of an upper screen 11a and a lower screen 11b, and by vibrating the upper screen 11a and the lower screen 11b with a motor (not shown), the mixture of wet coal ash and water can be separated according to particle size. In this embodiment, a sieve with a first particle size of 2.0 mm is used as the coarse upper screen 11a, and a sieve with a second particle size of 0.3 mm is used as the fine lower screen 11b. Note that the vibrating sieve 11 can omit the draining step in the next process by selecting appropriate specifications such as the shape and inclination of the vibration surface.
[0018] Therefore, the mixture of coal ash and water with a particle size of 2.0 mm or more (material of 2.0 mm or more) remains on top of the coarse upper mesh 11a (step S5), and the fine mixture of coal ash and water with a particle size of less than 2.0 mm that passes through the upper mesh 11a is further sieved by the lower mesh 11b (step S6).
[0019] The materials having a diameter of 2.0 mm or more remaining on the upper net 11a are not suitable for use as abrasives and are therefore not usable, and are therefore collected after being stored in a flexible container bag (step S11).
[0020] Meanwhile, the mixture of coal ash and water with a particle size of less than 2.0 mm and 0.3 mm or more (0.3 mm to 1.9 mm material) remains on top of the finer mesh lower screen 11b (step S6), and the mixture of finer coal ash (fine particles) and water with a particle size of less than 0.3 mm (material less than 0.3 mm) that passed through the lower screen 11b is received in the lower water tank 12 (step S7).
[0021] That is, the 0.3 mm to 1.9 mm material is bagged in a wet state and used as an abrasive. As described later, it is preferable that the mixture of coal ash and water bagged in a wet state is used in wet mud blasting (step S12).
[0022] The lower water tank 12 and the dehydration tank 13 are connected by piping, and the materials less than 0.3 mm in size are pumped from the lower water tank 12 to the dehydration tank 13 by the pump 23 (step S8). The materials less than 0.3 mm in size are then fed into the dehydration bag 13a arranged in the dehydration layer 13 and dehydrated.
[0023] Then, the water discharged from the dehydration bag 13a in the dehydration tank 13 is pumped back to the dissolution tank 10 by the pump 24. In this manner, the excess water in the dehydration tank 13 is circulated and reused.
[0024] (Wet mud blasting) Next, the configuration of the wet slurry blasting device T will be described with reference to Fig. 3. The wet slurry blasting device T is mainly composed of a water tank 31 for storing water, a built-in pump 32 for sucking water from the water tank 31 and pumping it to a pressurized tank 33, the pressurized tank 33 to which the water from the water tank 31 and the abrasive are supplied, an external compressor 34 for spraying the abrasive wrapped in water (wet slurry abrasive), and a nozzle 35 for spraying the wet slurry abrasive in a cyclone shape.
[0025] In this way, by using the wet slurry blasting device T, the abrasives can be turned into wet slurry by pressurizing the inside of the pressurized tank 33. That is, the abrasives are surrounded by water and turned into wet slurry. When this wet slurry abrasive is released from the nozzle 35 and hits the steel surface, the film of water surrounding the abrasives also envelops the paint, allowing it to be polished and cleaned.
[0026] In particular, according to the manufacturing method of the abrasive of the embodiment described above, the abrasive is manufactured in a wet state, so that the abrasive and water are already familiar with each other, and it is easier to maintain the wet granular mud state. In other words, when the abrasive is put into the pressurized tank 33, the abrasive already holds water, so that the water and the abrasive are efficiently mixed in the pressurized tank 33 and it is easy to turn into wet granular mud. In addition, because the abrasive is already in a wet state holding water, the amount of water supplied to the pressurized tank 33 can be reduced.
[0027] The wet slurry blasting method using this wet slurry blasting device T has the following technical features and effects. 1) By specifying the material type, particle size, and Mohs hardness of the non-metallic abrasive, the quality of Type 1 scraping specifications can be ensured. 2) By selecting the mixing ratio of water and abrasive, visibility is ensured by suppressing dust and preventing the scattering of harmful substances, and work safety is improved. Furthermore, it becomes possible to remove surface deposits, including salt, at the same time as base preparation. 3) The use of a volatile water-soluble rust inhibitor can prevent rust from recurring.
[0028] In this way, by using this wet slurry blasting equipment T, the abrasive covered in a film of water envelops the paint, rust, and harmful substances when it hits the steel surface, suppressing dust and preventing scattering, and simultaneously removing the adhering salt that is difficult to remove with the conventional dry blasting method, making it possible to process in one process. Furthermore, as a surface preparation method aiming for the use of high-quality Class 1 scraping, it can also reliably wet the surface to scrape off lead-containing paint films, which have become a problem in recent years.
[0029] More specifically, the wet slurry blasting method using the wet slurry blasting device T also has the following effects.
[0030] -Compact machinery equipment can suppress dust generation Conventional dry blasting methods scatter non-metallic abrasives and generate a lot of crushed dust, so they require large-scale equipment such as dust collection devices, temporary dust protection equipment, ventilation equipment, lighting equipment, etc. In contrast, the blasting method using wet slurry abrasives requires compact machinery and equipment, suppresses dust generation, and is superior in terms of cost and hygiene.
[0031] - Anti-rust primer treatment available Because a vaporizable water-soluble rust inhibitor is applied, it is possible to ensure quality until the anti-rust primer treatment of the ground surface. The application of a vaporizable water-soluble rust inhibitor suppresses the occurrence of rust reversion and protects the steel surface until the anti-rust primer treatment, so quality can be ensured within the four hours specified in the Steel Highway Bridge Corrosion Prevention Handbook. EXAMPLES
[0032] Next, with reference to Figs. 4 to 6, we will explain the applicability confirmation test that was conducted to confirm the particle size of the abrasive suitable for the wet mud blasting equipment. In this applicability confirmation test, abrasives with two different particle sizes were created for clinker ash and IGCC slag. Then, the effectiveness was confirmed in a blast test using the created abrasives. The particle size of the abrasives was the following two types.
[0033] Clinker ash: 1) 0.3mm~1.9mm, 2) 1.9mm or less IGCC slag: 1) 0.3mm~1.9mm, 2) 1.9mm or less
[0034] In the preparation of the abrasive, an efficient classification system is selected, and the classification effect and quality are confirmed by laboratory tests before and after classification. As explained below, a wet classification system is selected as a manufacturing method of abrasive suitable for wet granular slurry blasting equipment.
[0035] (1) Abrasive processing Clinker ash and IGCC slag generated at power plants were processed into wet grinding materials. In this blasting test to confirm the suitability of the abrasives, two types of abrasive particle size were used for both clinker ash and IGCC slag: 0.3mm to 1.9mm and 1.9mm or less. To prepare 0.3mm to 1.9mm abrasives (first process classification), a two-stage vibration sieve 11 was selected, with a 2.0mm screen on the upper stage and a 0.3mm screen on the lower stage. To prepare 1.9mm or less abrasives for the second process classification, a kneader was used to mix and stir a specified amount of the 0 to less than 0.3mm material generated in the first process classification with the first process classified material to prepare the abrasives.
[0036] (2-1) First step classification (2-2) Classification flow The equipment and steps described above with reference to Figures 1 and 2 are used.
[0037] (Consideration) Because a compact and simple wet-type vibrating sieve 11 was selected for the trial system, the material did not drain sufficiently when moving through the screen. If the material was directly packed in plastic bags, it would become excessively wet, so the material was packed in sandbags, and after the specified time of dehydration, the outside was sealed in a plastic bag.
[0038] By selecting the appropriate specifications for the shape and inclination of the vibrating surface of the vibrating sieve 11, the next step of draining can be omitted, making bagging more efficient.
[0039] The ratio of material to water in the dissolution tank 10 was 1:3. Although it was planned to circulate overwater, tap water was used in the first half of the process because there was little overwater. Partway through, the material separated due to the small amount of water in the dissolution tank 10, causing clogging. In the second half of the process, overwater was circulated, which allowed sufficient mixing and smooth pressure transfer of the material.
[0040] The relatively large shape and dimensions of the dissolution tank 10 also caused material separation when dissolving small amounts (mixing water and materials). In addition, it was necessary to constantly add water according to the conditions so that the water level did not drop below the agitator blades 10a. Therefore, it was necessary to select a dissolution tank 10 with an appropriate shape, size, and specifications.
[0041] The undercoat is 5m with excess water. 3 The slag is pumped into the dewatering tank 13 and dewatered in the dewatering FIBC 13a. At this time, fine slag flows out of the surplus water in the dewatering FIBC 13a. Therefore, the turbidity of the surplus water is high in the early stages of storage. However, the slag from the clinker ash and IGCC slag settles quickly in the water, and by the next day the supernatant water is at or below SS200, making it possible to discharge the water in compliance with sewerage discharge standards (less than SS600). Recycling the surplus water is important in order to reduce the amount of wastewater.
[0042] The time required for creating tare bags using the wet vibrating sieve 11 in this example was about 30 seconds to 1 minute and 30 seconds per bag, depending on the adjustment of the pumping amount by the inverter pump according to the situation.
[0043] (2-3) First step classification results The grain size composition of the materials delivered to the Taiho Construction Technology Research Institute and the first-stage classified materials was confirmed by simple sieving tests in the laboratory. The unit volume weight and moisture content were also confirmed by laboratory tests.
[0044] As shown in Figure 4(a), the particle size distribution of the clinker ash before classification (incoming material) was 6.7% over-material of 2.0 mm or more, while the first-classified material accounted for only 1.0%. Also, the IGCC slag before classification (incoming material) was 21.4% under-material of 0.25 mm or less, while the first-classified material accounted for only 1.3%. In other words, the over-material is mainly separated from the clinker ash by the first classification process, while the under-material is mainly separated from the IGCC slag by the first classification process, and the particle size is adjusted.
[0045] As shown in Fig. 4(b), the unit weight was measured before classification (incoming material) and was 0.852 g / cm for clinker ash. 3 The IGCC slag is 1.853 g / cm 3 It became.
[0046] As shown in Fig. 4(c), the moisture content of the first-class clinker ash was 35.6%, and that of the first-class IGCC slag was 2.2%.
[0047] (3-1) Second step classification The first process classified material was subjected to the following classification to prepare an abrasive material.
[0048] (3-2) Second process classification of clinker ash In order to remove under-materials of less than 0 to 0.3 mm from the first-stage classified abrasives, the abrasives were reclassified to produce abrasives of 0.3 to 1.9 mm.
[0049] ·Equipment used Hand mixer, 18L pail, 0.3mm sieve (used in a wet vibrating sieve)
[0050] Classification procedure 1) First process: Divide the classified material into 4 portions (approximately 5 kg) and place them into pails. 2) Water injection (abrasive:water=1:2) 3) Mix with a hand mixer (1 minute) 4) Emitted onto a 0.3mm screen 5) Recovery of classified materials 6) Sandbag and dehydrate four times 7) Repeat steps 1)-6) above to make 3 bags (approximately 60 kg).
[0051] (3-3) Second process classification of IGCC slag In the first step, the classified abrasive was mixed with under-material of 0 to less than 0.3 mm to create an abrasive of 1.9 mm or less.
[0052] ·Contamination amount From the results of the IGCC pre-classification particle size test (Figure 4(a)), Less than 2mm: 92.1%, Less than 0.25mm: 21.4% From the results of the particle size test after IGCC classification (Figure 4(a)), Less than 0.25mm: 1.3% Therefore, the material with a diameter of less than 0.25 mm in the 25 kg sample is 25kg x (21.4% / 92.1%-1.3% / 100%) ≒ 6kg required
[0053] Materials and equipment used Material: IGCC slag undermaterial of 0 to 0.3 mm that has settled in the lower water tank 12 of the wet vibrating sieve 11 Equipment: Kneading machine
[0054] Mixing procedure 1) First process: Prepare 19 kg of grinding material (0.3 mm to 1.9 mm) and 6 kg of under material (0 to less than 0.3 mm). 2) The above materials are simply mixed by hand, then put into a mixer and mixed automatically. 3) Open the bottom of the mixer, temporarily place it in a container, and then pack it in sandbags. 4) Repeat steps 1)-3) above to make 3 bags (approximately 75 kg).
[0055] (Consideration) When IGCC slag is wet classified into grinding materials of 1.9 mm or less, if a two-stage vibrating sieve (11) like the first process classification is used, the under material cannot be retained, and it passes through the sieve and accumulates in the lower water tank 12 together with the excess water. This time, this retained under material was added and mixed, but since this is not efficient, it is considered efficient if, for example, classification with one stage of a 2.0 mm sieve after grinding the material (in a wet state) is effective.
[0056] (3-4) Second step classification results A sieving test was carried out to examine the effect of reclassifying clinker ash, and it was confirmed that the hand mixer melting method had a high separation effect on clinker ash, as shown in Figure 5. Note that the test was omitted for IGCC slag, as it was mixed in at a fixed amount.
[0057] (4) Confirmation of the grain size of abrasives suitable for wet mud blasting equipment To confirm the particle size of the abrasives suitable for wet mud blasting equipment, two cases were prepared: one with a particle size in the same range as the pre-made product, and the other with a range including the under material. Blasting tests were carried out using the classified abrasives, using a 1m x 1m blackened steel plate and center material (painted film) from the Taito Construction Technology Research Institute as test specimens.
[0058] (Consideration) In terms of their evaluation as blast abrasives, all of them met the quality standard of Sa1 1 / 2 for paint stripping. In terms of application efficiency, clinker ash is porous and softer than IGCC slag, so application time was long and efficiency was low.
[0059] As shown in Figure 6, the results of the difference in particle size range showed that the construction time was shorter when the under material was included for both clinker ash and IGCC slag. The amount of material consumed per construction area was almost the same. The reason for this is that, since the pressure settings were not changed, the inclusion of under material improved fluidity, resulting in a larger amount of blast injection per hour.
[0060] (effect) Next, the effects achieved by the method for producing an abrasive according to the present embodiment will be listed and described. (1) As described above, the manufacturing method of the abrasive of this embodiment includes a step of preparing coal ash, a step of adding water to the coal ash and stirring the coal ash, a step of classifying the coal ash that has been added with water and stirred, and a step of bagging the classified coal ash. By including these steps, the abrasive can be manufactured while the coal ash, which is the raw material, is in a wet state without drying it.
[0061] (2) In addition, the process of bagging coal ash involves bagging the coal ash while it is still wet, which not only reduces dust generation during the manufacturing process, but also reduces dust generation when using adjusted coal ash as an abrasive. Furthermore, when used with the wet slurry blasting equipment T, it is compatible with moisture and reduces the amount of water used.
[0062] (3) Furthermore, in the process of classifying the coal ash, a two-stage vibrating sieve 11 consisting of an upper screen 11a and a lower screen 11b is used as a wet classifier, so that over-materials coarser than a predetermined first particle size and under-materials finer than a second particle size smaller than the first particle size are removed. This makes it possible to adjust the particle size efficiently and with high accuracy.
[0063] (4) In addition, it is also preferable that the step of classifying the coal ash uses a single-stage vibrating sieve (11) consisting of only an upper screen (11a) as a wet classifier so that over materials coarser than a predetermined first particle size are removed. In this way, it is possible to adjust the particle size more efficiently and with high accuracy.
[0064] (5) In addition, confirmation tests were conducted using clinker ash as coal ash, and it was confirmed that clinker ash, which had not previously been used as an abrasive, can now be used as an abrasive.
[0065] The moisture content of this classified clinker ash is greater than 30%, which improves its compatibility with water and allows for reduced water consumption during use.
[0066] (6) In addition, by conducting confirmation tests using IGCC slag as coal ash, it was confirmed that IGCC slag, which had not previously been used as an abrasive, can now be used as an abrasive.
[0067] The moisture content of this classified IGCC slag is less than 5%, which allows it to mix well with water while reducing its weight during transportation.
[0068] Other configurations and effects are substantially the same as those of the above-described embodiment, and therefore description thereof will be omitted.
[0069] Although an embodiment of the present invention has been described in detail above with reference to the drawings, the specific configuration is not limited to this embodiment, and design changes that do not deviate from the gist of the present invention are included in the present invention.
[0070] For example, in the embodiments, the case where clinker ash and IGCC slag are used as coal ash, which is the raw material for the abrasive, is described, but this is not limited thereto, and the manufacturing method of the abrasive of this embodiment can also be applied to other types of coal ash. [Explanation of symbols]
[0071] S Abrasives manufacturing system 10 Dissolution tank 10a Agitator blade 11 Vibrating sieve 12 Lower water tank 13 Dehydration tank 13a Dehydration bag 21 Motor 22~25 Pump T Wet mud blasting equipment 31 Water Tank 32 Built-in pump 33 Pressurized Tank 34 External Compressor 35 Nozzle
Claims
1. A method for manufacturing an abrasive using coal ash as an abrasive, in which when wet-particle muddy coal ash collides with a workpiece surface by a blasting method, a film of water surrounding the coal ash also envelops the paint applied to the workpiece surface that is the target of the blasting method, thereby polishing and cleaning the surface, the method comprising the steps of: preparing coal ash; adding water to the coal ash and stirring the same; A step of classifying the coal ash that has been added with water and stirred; packing the classified coal ash in a wet state; A method for producing an abrasive comprising the steps of:
2. 2. The method for manufacturing an abrasive material according to claim 1, wherein the step of classifying the coal ash uses a wet classifier to remove over materials coarser than a predetermined first particle size and under materials finer than a second particle size smaller than the first particle size.
3. 2. The method for manufacturing an abrasive according to claim 1, wherein the step of classifying the coal ash uses a wet classifier to remove over materials coarser than a predetermined first particle size.
4. The method for producing an abrasive according to claim 1 , wherein the coal ash is clinker ash.
5. The method for producing an abrasive according to claim 1 , wherein the coal ash is IGCC slag.
Citation Information
Patent Citations
Test drier for grain
JP1988094132A
Abrasive for blast processing
JP2004307695A
Blast material and blasting method
JP2012121121A